The ROLE OF FAMILY SUPPORT MEDIATION AND SHARIA FINANCIAL INCLUSION IN THE PERFORMANCE OF WOMEN'S MSMES IN DKI JAKARTA - Asep Maksum; Hanny Nurlatifah; Muhammad Emil Rachman; Idrus Ramadhan (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2026)
The purpose of this study is to determine the role of Islamic Financial Literacy (IFL), Digital Literacy (DL), and Leadership Style (LS) with the mediating role of Islamic Financial Inclusion (IFI) and Family Support (FS) for the performance of women's MSMEs. This study uses a quantitative method with a sample of 100 female MSMEs in Jakarta. Data processing using Smart PLS analysis 4. The novelty of this study is that it combines sharia financial literacy, digital literacy, and leadership style simultaneously as factors influencing the performance of women MSMEs in urban areas, and uses two mediators at once—sharia financial inclusion and family support—in the relationship between literacy and leadership and the performance of female MSMEs. The conclusion produced is that the results of the research are that the variables of Islamic financial inclusion can mediate Islamic financial literacy and leadership style for the performance of women MSMEs in DKI Jakarta. Meanwhile, family support cannot be a mediator of Islamic financial inclusion, Islamic financial literacy, digital literacy, and leadership style for the performance of women's MSMEs in DKI Jakarta